A Deliberate Practice‐Based Ultrasound Training Program for Fetal Palate Screening Using a Sequential Sector Scan Through the Oral Fissure. (11th November 2022) - Wan, Ying; Zhou, Yi; Li, Liang; Gao, Chuanfen; Fan, Min; Qin, Jing; She, Jingwen; Zhang, Chaoxue
Abstract : Objectives: To introduce an ultrasound training program for fetal palate screening by using a sequential sector scan through the oral fissure to train less experienced doctors and to investigate its effectiveness. Methods: Twenty doctors and several women at approximately 20–28 weeks of gestation with singleton pregnancies who provided informed consent were enrolled. The training program consisted of theory and practice training, several tests, and two surveys. Trainees were tested before training and immediately after training; for the latter, each item with a score that was less than 60% of the full score was again used for training with a reconstructed plan. Finally, a post‐training test was completed. Results: The median theory scores, median practice scores, median language competence scores, and median self‐assessment scores all increased significantly from the pre‐training to post‐training tests ( P  < .01). The median completion time for fetal palate scans decreased significantly from the pre‐training to post‐training tests ( P  < .01). The median questionnaire scores were 5.00 for pragmatism, 4.00 for content, 4.00 for scientific nature, and 5.00 for effectiveness. Conclusions: The training program for fetal palate screening can effectively standardize and improve doctors' scans for fetal palates. In addition, the program feasibly allows for the incorporation of the scan sequence into fetal palate screening.